Comparative Analysis of Levels of Iron, Copper, Transferrin, and Ceruloplasmin in Serum of the Patients of Psoriasis - Shabir Ahmed Orakzai, Ambareen Ali, Nayaab Sarwar, Shabir Hussain, Tehseen Naveed, Muhammad Farooq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To conduct a comparative analysis on the serum levels of transferrin, ceruloplasmin, copper, and iron in the serum of patients suffering from psoriasis. Methodology: It was a case-controlled comparative study conducted on a group of 40 individuals suffering from psoriasis, and another group of 40 healthy individuals. The levels of iron, copper, ceruloplasmin, and transferrin in serum were evaluated directly. The severity of the disease was observed by psoriasis area and severity index (PASI), and the association between PASI score and disease severity. Results: The study involved 40 psoriatic patients, and 40 healthy individuals, and it was observed that iron, and transferrin levels were statistically low in the patients suffering from psoriasis as compared to healthy individuals. However, there was no significant difference observed between the two groups in terms of levels of copper in serum. Conclusion: The study concluded that there is an involvement of trace elements in the serum of psoriatic patients.